2019
DOI: 10.1111/aogs.13515
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic nervous system response to acidosis: Evaluation in an experimental fetal sheep model

Abstract: | INTRODUC TI ONThe occurrence of decreased maternal-fetal gas exchange during labor may lead to fetal acidosis, which can be responsible for severe neonatal complications including a risk of cerebral palsy. It is recognized that about 10% of cases of cerebral palsy are caused by peripartum asphyxia. 1 Recent guidelines highlighted the importance of knowledge of fetal physiology to improve the interpretation of fetal heart rate (FHR) changes during labor. 2 However, changes in FHR are an imperfect reflection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
1
23
2
Order By: Relevance
“…In the present study, parasympathetic blockade by either bilateral cervical vagotomy or atropine sulfate infusion essentially abolished FHRV between brief repeated UCOs, which were designed to mimic the pattern of fetal hypoxemia during labor. These findings demonstrate that the increase in measures of FHRV observed early during more prolonged paradigms of repeated UCOs (12,17,26,31,49) is entirely mediated by increased parasympathetic activity. The combination of the present findings with our previous studies of the roles of the R548 PARASYMPATHETIC REGULATION OF FHRV neural and adrenal sympathetic systems (25,26) strongly confirms that SNS control of FHRV is acutely suppressed after acute fetal hypoxemia, leaving the parasympathetic nervous system as the key regulator of FHRV during labor-like hypoxia.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the present study, parasympathetic blockade by either bilateral cervical vagotomy or atropine sulfate infusion essentially abolished FHRV between brief repeated UCOs, which were designed to mimic the pattern of fetal hypoxemia during labor. These findings demonstrate that the increase in measures of FHRV observed early during more prolonged paradigms of repeated UCOs (12,17,26,31,49) is entirely mediated by increased parasympathetic activity. The combination of the present findings with our previous studies of the roles of the R548 PARASYMPATHETIC REGULATION OF FHRV neural and adrenal sympathetic systems (25,26) strongly confirms that SNS control of FHRV is acutely suppressed after acute fetal hypoxemia, leaving the parasympathetic nervous system as the key regulator of FHRV during labor-like hypoxia.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, increased intrapartum STV has been associated with increased fetal scalp lactate levels (32), and increased FHRV on visual inspection was associated with an increase in risk of acidemia at birth (39). Systematic studies in fetal sheep have demonstrated that fetal compromise can be associated with both increased and suppressed FHRV (12,17,26,31,49). Our understanding of both the clinical utility and physiological underpinnings of intrapartum FHRV remains surprisingly incomplete despite FHRV being a critical, routinely used index of fetal wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…This model is especially important as one of the few that allows for continuous fetal monitoring by in utero instrumentation [17,18,19]. Maternal and fetal telemetric or electrocardiographic leads and catheters (arterial, venous, umbilical, and amniotic) can be surgically placed to continuously monitor metabolic activity, nutrient and gas exchange, and cytokine presence, and to frequently obtain physiologic measurements and biological samples at the maternal–fetal interface [20,21,22,23]. The ability to closely monitor the maternal–fetal interface has led to the extensive use of sheep as model for human pregnancy and fetal development over the last half a century, and has contributed to an understanding of fetal stress and intrauterine growth restriction—both of which are components of maternal ZIKV infection and CZS [17,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Our team developed the fetal stress index (FSI) based on an original HRV analysis method 11 that combined time and spectral analysis 10 . In previous experimental studies using a model of repeated cord occlusion in fetal sheep, we demonstrated that this index was related to variations in parasympathetic activity 11 and correlated with acid‐base status 13 . Such a biomarker may constitute a new pathway for evaluating fetal well‐being during labor 14 …”
Section: Introductionmentioning
confidence: 84%